THE IMPLEMENTATION OF PROBLEM BASED LEARNING TO IMPROVE STUDENTS’ FORMAL REASONING AND PHYSICS PROBLEM SOLVING ABILITY - YULIAWATI, OKTA; , WASIS (Inovasi Pendidikan Fisika, 2018)
The aim of this study was to describe the results of implementation problem based learning. The study was pre-experimental design by using one group pre-test and post-test design. The participants included students from grade X MIA 6 as experimental class, X MIA 7 and X MIA 8 as replications class. Data was collected by observation and test. Data was analyzed using learning activities analysis, assessment of test result analysis with descriptive analysis, paired t-test, n-gain score and correlation analysis. The result showed that: (1) the implementation of problem based learning carried out very well, (2) students? formal reasoning ability improved from initial formal level towards formal level, (3) students? problem solving ability improved significantly with n-gain score which categorized as moderate level, (4) the correlation between students? formal reasoning and problem solving ability was in moderate positive correlation. Based on the results, it can be concluded that the implementation of problem based learning can improve students? formal reasoning and physics problem solving.